The Regulation Effect of Team Leadership and Cohesion on Athletes' Sports Grade - Maozhu Jin; Yucheng Zeng; Haizhen Huang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Team cohesion is a crucial element in bringing the group together. Team cohesion is the engine that drives the progression of a sports team, and it plays a crucial part in boosting the team's confidence and overall performance. This study aims to investigate the connection between athlete leadership and team cohesion and the potential mediating and regulating effects between emotional infection and sports grade. The Athlete Leadership Questionnaire, Group Environment Questionnaire, and Emotional Infection Scale were administered to 316 athletes, and the data were analyzed using SPSS. The Bootstrap approach was used to determine whether emotional infection significantly mediated the link between athlete conduct and team cohesion. In the main effect, athlete leadership can positively and significantly predict team cohesion (β=0.531, p<0.01), and the interaction item between athlete's leadership and sports level also reached a significant level (β=0.355, p<0.01). Age and sex did not pass the F test (F=1.148, p>0.05), indicating that they will not affect group cohesion. This study found that team cohesiveness and external leaders had the most impact on social cohesion, but social leaders had the greatest impact on task cohesion. In addition, the study found that emotional infection serves as a partial mediator between the leadership of athletes and their numerous aspects and team cohesion.